Recursivity and Transcendence: A Neurophenomenological Analysis of "Mon Chalo Nijo Niketane" as an Ontogenetic Framework for Consciousness - Pallathadka, Harikumar; Roy, Parag Deb; Sarkar, Rita; Saha, Jayshree; Saikia, Jugasmita (Stallion Journal for Multidisciplinary Associated Research Studies, 2025)
This paper presents a novel theoretical framework for understanding consciousness through an interdisciplinary analysis of the Bengali devotional song "Mon Chalo Nijo Niketane" ("O Mind, Return to Your True Abode"), historically associated with Swami Vivekananda. By integrating third-generation cognitive science, quantum neurodynamics, contemplative phenomenology, and enactive approaches to cognition, we demonstrate how this devotional expression anticipates contemporary advancements in consciousness studies. We propose the Recursive Self-Integration Model (RSIM), which conceptualizes consciousness as a dynamic, self-organizing system characterized by nested hierarchies of recursive processing that transcend traditional subject-object dichotomies. This model resolves several persistent theoretical challenges in consciousness studies, including the binding problem, the explanatory gap, and the hard problem of qualia. Through rigorous phenomenological analysis and theoretical synthesis, we demonstrate that the inward journey articulated in this devotional tradition offers a sophisticated ontogenetic framework with profound implications for understanding the structural invariants of conscious experience. Our comprehensive analysis includes empirical correlates from neuroimaging studies, computational modeling approaches, and first-person phenomenological investigations that collectively support the RSIM framework. This research contributes to an emerging paradigm that transcends conventional materialist and dualist approaches to consciousness through a non-reductive, dynamical systems perspective with significant implications for clinical psychology, education, artificial intelligence, and environmental ethics.